STUDENTS’ SELF-EFFICACY IN CONFRONTING CHANGES OF THE FORM ON THE FINAL PROJECT DURING COVID-19 PANDEMIC - Eka Cahya Maulidiyah; Khabibur Rohman (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2022)
Among changes that occur in education, especially in universities, COVID-19 pandemic affects on the change of form on final project as a requirement for student graduation. Some universities no longer require students to write thick and complex thesis as a graduation requirement, but they switch to write articles published in scientific journals. By then, the present study aims to see how is the self-efficacy of final year students in responding to the policy. This study implements quantitative descriptive research design. The researchers measure the student self-efficacy using a scale adapted from academic self-efficacy consisting of 23 items. The results showed that final year students were not familiar enough with reading and writing scientific articles. As many as 50.98% of respondents admitted that they rarely read scientific articles. There were even 29.41% of respondents who had never written scientific papers before. Interestingly, the average score of students’ self-efficacy in writing scientific papers is quite high, which is 65.5. High self-confidence without being supported by qualified abilities will make scientific articles produced less than optimal. The results of this study can be used as a basis for lecturers and policy makers at universities, in order to familiarize students with reading and writing scientific articles